Avaliação de um programa de formação docente sobre inclusão escolar aliando ensino colaborativo e diferenciado - Santos, Keisyani da Silva (2021)
: Initially the basic premise of Special Education was that its target audience students would benefit from a unique body of knowledge that were intended for them if they studied in small classes and in separate environments, applying specific methodologies. Currently, evidence indicates that the success of school inclusion policies is more related to the changes that benefit all students, that is, universal pedagogical measures aimed at improving the quality of teaching. Two promising proposals evidenced in the literature stand out, because they favor the learning and participation of all students, are: coteaching as a service model that involves the partnership between teachers of common and special education working with the whole class; and, the differentiated teaching theoretical-practical reference for the organization of teaching from the recognition and valorization of diversity. In this context, from change of conception to teacher education is a fundamental element for dissemination of this knowledge and possible impact on the schooling of Special Needs Education. Thus, the present study aimed to develop, implement and evaluate a teacher training program, in service, combining the proposals coteaching and differentiated teaching. Based on the theoretical and methodological assumptions of Collaborative Research, a program was planned, implemented and evaluated for 18 teachers, from a municipal education network in the interior of São Paulo, composing nine pairs of teachers (from common and special education), with the proposal of acting in partnership, in heterogeneous classes that contained at least one PAEE student, of early childhood education or in the early years of elementary school. The study was developed in three stages: I) Development of the Teacher Training Program; II) Implementation of the program, and III) Evaluation of the Program. Data collection took place in all the mentioned stages, held in a face-to-face environment, with monthly meetings in 2018, and in a virtual environment, with activities developed between face-to-face meetings. Data related to face-to-face meetings were collected and recorded through field journals, videos and artifacts produced during the activities by the pairs. The data collected in a virtual environment was recorded and archived in the virtual learning environment itself. The analysis of the collected material was based on the procedures of codification and categorization into thematic axes, having as reference the objectives of the study. The main results showed that there was conceptual evolution of the two proposals by the participants throughout the training, since at the end of the program they demonstrated theoretical appropriation basic concepts and assumptions. The practical activities of: evaluating students, planning and executing classes, incorporating co-teaching and differentiated teaching enabled articulation with theory. The objective of experiencing the proposals of co-teaching and differentiated teaching, together, was achieved only by some pairs, who had more favorable working conditions for their development, especially compatibility of schedule for planning and execution of classes and support of the coordination of the school unit. The pairs that did not have these conditions partially exercised the proposals or did not experience them. In the evaluation of the program, by the participants, the content was considered relevant and feasible for application in the classroom, the other issues were evaluated satisfactorily. The experiences analyzed contribute to the reflection of effective pedagogical practices that contemplate the diversity of students in daily school life and for teacher education. Finally, it is considered that the proposals of co-teaching and differentiated teaching, although independent complement each other, can enhance each other. The program showed potential for theoretical and practical training for teachers.